(untitled) (Czech Journal of International Relations, 2024)
Edvard Beneš, Czechoslovak and European politician. A collection of essays. Jiří z Poděbrad Foundation, Prague 1994, 118 pages. Amelie Posse-Brázdová: Secret Letters from Prague 1948. Library of the Edvard Beneš Society, vol. 6, Prague 1994, 92 pages, ISBN 80-901-733-1-4. Josef Hanzal: Edvard Beneš. Who is, vol. 7, Mladá fronta, Prague 1994, 56 pages, ISBN 80-204-0445-7. Karel Kaplan: The Last Year of the President. Edvard Benes in 1948. Publishing house Doplněk in cooperation with the Institute for Contemporary History of the CAS, Brno 1994, 176 pages, ISBN 80-85765-31-4. Alexandr Ort: Edvard Beneš, diplomat and politician. IRMA, Prague 1994, 88 pages, ISBN 80-901353-1-5.